Integration among unequals: How the heterogeneity of European varieties of capitalism shapes the social and democratic potential of the EU - Martin Höpner; Armin Schäfer (Max Planck Institute for the Study of Societies, 2012)
At first glance, the social purpose and the democratic potential of the EU have made progress in the last 15 years. However, this impression is misleading. We argue instead that the social and democratic potentials of the EU are crucially shaped by the heterogeneity of European varieties of capitalism. First, we locate our argument in the integration literature and argue that political-economic heterogeneity shapes not only intergovernmental bargains but also the opportunities for judicial integration. Second, we document the heterogeneity among European varieties of capitalism and how it has increased with each round of enlargement. Third, we show how the heterogeneity of political-economic interests has led governments to opt for autonomy-protecting solutions whenever European initiatives have targeted highly sensitive institutions that constitute their different political-economic regimes. Fourth, we also show that, despite this, the European Court of Justice (ECJ) has often overruled such autonomy-protecting measures by extending the reach and scope of the European fundamental freedoms. We conclude, fifth, that the asymmetry between market-enforcing and market-restricting integration is not likely to disappear in the near future, and that the heterogeneity of European varieties of capitalism limits not only the social but also the democratic potential of the EU. – – Auf den ersten Blick scheinen sich die sozialen und die demokratischen Potenziale der EU in den vergangenen fünfzehn Jahren vergrößert zu haben. Doch dieser Schein trügt. Denn diese Potenziale werden in erheblichem Maße von der Heterogenität der europäischen Spielarten des Kapitalismus geprägt. Diese Argumentation verorten wir zunächst in der Integrationsliteratur und verdeutlichen, warum die politökonomische Heterogenität der EU-Mitgliedsländer nicht nur die Ergebnisse intergouvernementaler Verhandlungen, sondern auch die Möglichkeiten der judiziellen Integration beeinflusst. In einem zweiten Schritt dokumentieren wir die politökonomische Heterogenität der EU und ihre Zunahme im Zeitverlauf anhand von Daten. Drittens zeigen wir, dass die Mitgliedstaaten häufig autonomieschonende Lösungen wählten, wenn europäische Initiativen auf die Transformation politökonomisch sensibler Institutionen zielten. Viertens führen wir vor, wie der Europäische Gerichtshof (EuGH) genau diese autonomieschonenden Lösungen immer wieder konterkarierte, indem er die europäischen Grundfreiheiten immer extensiver interpretierte. Im Ausblick verdeutlichen wir, dass die Asymmetrie zwischen marktschaffender und marktkorrigierender Integration auch in Zukunft nicht verschwinden wird, und legen dar, warum die politökonomische Heterogenität nicht nur das soziale, sondern auch das demokratische Potenzial der EU prägt.
Keywords: 300; Europäische Integration; Varieties of Capitalism; Public Choice; EU-Staaten